(untitled) (American Journal of Interdisciplinary Research and Development, 2024)
The article discusses ways to improve the efficiency of fruit vegetable production in Uzbekistan. As a result of the analyzes, the effectiveness of fruit vegetable products grown in the Andijan region was studied.